The need for improved financial reporting of a developing country energy utility - Brown, Alistair (Elsevier, 2016)
Some consideration has been given to regulatory and institutional reforms to facilitate sustainable development in electricity usage in Papua New Guinea but little attention has been paid to bringing about full compliance of financial reporting expectations of the country׳s main energy utility. Examining documentary evidence of the audit reports of the Auditor General׳s Office of Papua New Guinea, this study considers the financial reporting compliance of PNG Power for the period 2007–2013, and the means by which compliant reporting may be improved. The results of the study reveal that the financial statements of PNG Power are late and receive disclaimers of opinion from the Auditor General׳s Office, which suggest that PNG Power׳s stakeholders are not receiving accurate and reliable financial information to make informed decisions about sustainable development of electricity usage and planning in Papua New Guinea. The study reveals that it would take little resources to improve PNG Power׳s reporting, which in turn could enhance national energy policy decision-making and energy utility accountability.